Printed periodic waveguide structures : full-wave characterization, guided-wave characteristics and applications - Singh, Kshetrimayum Rakhesh (2008)
Printed periodic waveguide structures are investigated for applications in waveguide based band pass filters, electromagnetic band gap (EBG) structures and double negative (DNG) metamaterials. Such waveguide structures are characterized using the Hybrid Mom-Immittance Approach in which Immittance Approach is employed for calculation of spectral dyadic Green's functions for multilayered waveguide structures. Method-of-moments (MoM) is utilized for solving unknown current densities on printed strips/slots and Mode-matching Method has been used for obtaining reflection and transmission coefficients for various waveguide discontinuity elements.